Improving Legislative Performance by Strengthening Authority and Increasing Obligations - Shelvi Rusdiana (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2022)
The Regional Representative Council (In Indonesia: DPD/Dewan Perwakilan Daerah) is a government institution formed with noble intentions, to strengthen the representation of regional people so that their issues are fought for in the central government. However, in actual political practice, DPD is constrained by existing regulations in Indonesia, making DPD a legislative body without a clearly defined function and authority, and causing its inability to help increase the output of legislation. The legislature's performance, which increasingly often receives negative comments from the public, is a wake-up call for the Indonesian parliament to improve. This study aims to analyze the legal facts of the chaos of the Indonesian constitutional system that is not optimal in utilizing existing institutions such as DPD. This study also purposes to strengthen the urgency in correcting the mess through legal reform at the constitutional and legislative levels. The normative juridical legal method was used to investigate this matter, which refers to the positive regulations or laws that have been in force in Indonesia, which regulate the Indonesian constitution. As an institution with great potential for assisting the function of the House of Representatives (hereafter called DPR/Dewan Perwakilan Rakyat), DPD has always been neglected by Indonesian constitutional law politics according to this study. This research highlights the problems restricting the Indonesian government in connecting, understanding, and most importantly solving the problems that effect the lives of local communities, and how DPD has the potential to fix if given a better position in the legislation system.